Redefining Religious Moderation Education for Urban Muslim Youth - Jati, Wasisto; Bachtiar, Hasnan (Badan Litbang dan Diklat Kementerian Agama RI, 2024)
Religious moderation has been a government policy since 2015, aimed at countering radicalism and extremism. However, the hierarchical implementation of the program has led to the labeling of